Mindfulness y burnout en trabajadores de salud mental - Cino Fernandez, Caterina (2021)
Burnout is a common problem within mental health workers due to the stressors to which they are continuously exposed and implies a series of consequences for both the professional who suffers it and for their patients. The present study aimed to know the relationship between burnout and mindfulness in mental health workers. For this, a systematic search was carried out following the indications of the PRISMA guidelines (Urrútia &Bonfill, 2013) in Scopus, ScienceDirect and PubMed databases. Studies that related both variables in mental health workers and met all the inclusion and exclusion criteria (n = 7) were selected for the analysis. The results showed that there is a significant negative relationship between burnout and mindfulness in mental health workers. These results allow to consider mindfulness as a possible alternative treatment for burnout in mental health workers.